Application of psychological intervention combined with five-tone music therapy for patients undergoing colonoscopy (心理护理干预联合五音疗法在结肠镜检查患者中的应用) - LI Yanlin (李艳林); TANG Ling (唐玲); QI Huan (祁欢); CHEN Moyan (陈默岩); XU Bing (许冰) (Association of Integrative Nursing, 2023)
Objective To investigate the effect of psychological intervention combined with five-tone music therapy on relieving anxiety and depression of patients undergoing colonoscopy. Methods Totally 100 patients undergoing colonoscopy were randomly divided into the control group and observation group, with 50 cases in each group. All patients received routine care during the diagnostic colonoscopy, and those in the observation group were given psychological intervention combined with five-tone music therapy. The Self-rating Anxiety Scale and Self-rating Depression Scale were used to measure the emotional status of patients, and self-made questionnaire was used to evaluate the patient satisfaction with nursing service. Results Scores of SAS and SDS in the observation group was lower than those in the control group after colonoscopy(P＜0. 05). The satisfaction rate in the observation group was higher than that in the control group (96. 00% vs. 84. 00%, P＜0. 05). Conclusion Patients undergoing colonoscopy are more vulnerable to anxiety and depression. The psychological intervention combined with five-tone music therapy is potentially effective to relieve the anxiety and depression status of patients, and improve their satisfaction with nursing service. (目的 探讨心理护理干预联合五音疗法对结肠镜检查患者焦虑、抑郁情绪的影响。方法 选取2021年6月-12月来院接受结肠镜检查的100例患者为研究对象, 随机分为对照组和观察组。对照组给予常规护理, 观察组在常规护理的基础上给予心理护理及五音疗法。对比结肠镜检查前后两组患者焦虑自评量表(SAS)评分和抑郁自评量表(SDS)评分, 评价患者满意度。结果 肠镜检查后, 观察组SAS评分及SDS评分均低于对照组, 差异有统计学意义(P＜0. 05); 观察组满意度96. 00%(48/50), 高于对照组的84. 00%(32/50), 差异有统计学意义(P＜0. 05)。结论 患者在接受肠镜前存在焦虑、抑郁心理状态, 将心理护理及五音疗法应用于结肠镜检查过程, 可有效改善患者的焦虑、抑郁情况, 提高患者对护理的满意程度。)